Efficiency Analysis Of Islamic Rural Banks (BPRS) In Bengkulu And Lampung Provinces Using The Data Envelopment Analysis Approach - Cahyono, Andi; Setiawan, Romi Adetio; Kaemah, Tolan; Mufanti, Restu (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2025)
Purpose: This study analyzes the efficiency of Islamic Public Financing Banks (BPRS) in Bengkulu and Lampung Provinces during 2019–2023 by examining two BPRS in Bengkulu and four BPRS in Lampung with the largest assets and operating for more than five years.Design/methodology: This research employs a quantitative approach using financial reports of BPRS in both provinces. Samples were determined through purposive sampling based on asset size and operational period. Efficiency was measured using the Data Envelopment Analysis (DEA) method, which applies a linear programming system to construct a non-parametric frontier. The input variables were Third-Party Funds (DPK) and Operational Costs, while the output variables consisted of Fixed Assets, Financing, and Operational Income..Findings: The results indicate that several BPRS experienced inefficiencies. In Bengkulu, BPRS Maslahat Dana Syariah Nusantara was inefficient in 2022 due to high operational costs (+10.03%), low financing (-84.20%), and reduced operational income (-78.36%) caused by the COVID-19 pandemic. In Lampung, inefficiency was found in BPRS Kota Bumi (2019) due to high costs (-12.13%) and suboptimal financing and income; BPRS Metro Madani (2021–2022) due to rising costs (+4.51%) and mismatched financing growth; and BPRS Lampung Timur (2020) due to declining income (-4.91%). Overall, Lampung BPRS demonstrated higher efficiency, with an average score of 0.85 compared to Bengkulu’s 0.70, attributed to broader market access and stronger financial performance in urban-based BPRS.Practical Implication: The study highlights key challenges affecting BPRS efficiency, such as frequent regulatory changes and the economic impact of the COVID-19 pandemic. Strengthening fund allocation, improving cost management, and leveraging government policies on financial inclusion can enhance efficiency and market competitiveness.Originality/Value: This research provides new insights into the efficiency of BPRS in Bengkulu and Lampung by comparing their performance within a regional context. The findings underscore the strategic role of BPRS in supporting financial inclusion and ensuring compliance with sharia principles, while offering recommendations for improving operational sustainability